Level of Knowledge and Readiness of FPTV Final Year Students on Industrial Revolution 4.0 - RAZALI, NIZAMUDDIN; Razali, Muhammad Shah Iman; Rahim, Mohd Bekri; Yunus, Faizal Amin Nur; Abdul Rahman, Khairul Anuar; Gerijih, Debie Devisser Gerijih1 (Research and Innovation in Technical and Vocational Education and Training, 2021)
The industrial revolution 4.0 was a continuation of the increasing automation along with internet networks and other physical processes. These new technologies include automation, simulation, analysis and big data, robotic applications and the Internet of Things (IoT). This creates a new work environment that shows minimal use of human labor as a result of competition for human capital. Knowledge and readiness are the factors that must be emphasized to facing the challenges of this industrial revolution 4.0. Lack of creative and innovative thinking and incompetence in the field of study indicate lack of knowledge and readiness for ir 4.0. This study aims to identify the level of knowledge and the level of readiness among FPTV students and the relationship between these two level in the face of the current industry revolution 4.0. By quantitative research were performed and data collection based on the method of questionnaire was used. The study sample is FPTV final year students in all courses. A total of 144 questionnaire forms were completed and analyzed using the spss 25.0 program. The results show that the level of knowledge of industrial revolution 4.0 is high level with mean score 4.52. Further findings on the level of readiness for the industrial revolution 4.0 also show a high level with mean score 4.14. Meanwhile, there is a significant relationship between the level of knowledge and the level of student readiness in IR 4.0 but at low relationship. In conclusion, FPTV final year students have prepared themselves with the relevant knowledge and skills to become quality human capital to withstand the changing industrial revolution.